PRANATA MANGSA JAWA (Cermin Pengetahuan Kolektif Masyarakat Petani di Jawa) - Ali Badrudin (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
The research studies the Javanese language in the context of it society. The main goal is to express the knowledge system and the thought patterns of the Javanese society, especially the Javanese farmers, in understanding their life and the world of their life. The steps of this research are: (1) collecting data, (2) analyzing data, and (3) presenting the research results. The analysis of the data finds the following results: (1) The language units classification pattern are analyzed grammatically; (2) the knowledge system and the collective thought of the Javanese society expressed in the pranata mangsa are as follows: (a) The uses of metaphor describes: the world/the earth, (parts of) human body, wind, sounds, finery, water, and family relationship; (b) The reasons of using the Kawi language in pranata mangsa are motivated by the intellectual values, the artistic values, aesthetic aspects, and common usage in the Javanese literature; and (c) In relation to pranata mangsa, the Javanese society has the concepts of the vertical and horizontal relationship, which cover: the concept of God, the world/the earth, time, and space. Through pranata mangsa, the farmers harmonizing themselves with the cosmos and the nature.